METODE TAFSIR AL-QUR’AN; ANALISIS KEUNTUNGAN TANTANGAN DAN PERBANDINGAN ANTARA ERA DIGITAL DAN TRADISIONAL - Hasibuan, Rizky Ahmadi; Hasibuan, Badai Husain; Mujahid, Said (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Technological developments in the digital age have brought about major changes in the way people study, understand and access the Qur'an. With the advent of various digital platforms, the traditional method of tafsir, which used to be done through physical encounters and printed texts, is changing. Muslims can study the Qur'ān more easily and widely through tafsir available in the form of apps, websites and social media. Among the features that make these tafsir methods more interactive are verse searches, translations in multiple languages, and access to contemporary and classical commentaries. Traditional methods include thematic, tahlili, and analytical commentaries that rely on oral and written explanations. Digital methods use interactive and visual platforms such as YouTube and social media to enhance understanding. This article discusses the impact of digital technology on the development of tafsir methods. It covers advantages such as convenience and speed, as well as issues such as verification of tafsir authority and the possibility of misinterpretation caused by the spread of inaccurate information. It also emphasizes how important it is for scholars to use technology to ensure that Qur'anic exegesis is correct and pure in the digital age.